2020
DOI: 10.1002/clc.23331
|View full text |Cite
|
Sign up to set email alerts
|

Impact of leaflet thrombosis on hemodynamics and clinical outcomes after bioprosthetic aortic valve replacement: A meta‐analysis

Abstract: Background: Leaflet thrombosis (LT, also called cusp thrombosis) detected by multidetector computed tomography (MDCT) is common in bioprosthetic aortic valve replacement (bAVR). However, it remains contradictory whether MDCT-defined LT following bAVR is associated with hemodynamic deterioration and stroke. Thus, we performed the first meta-analysis to assess hemodynamic outcomes and updated the latest researches on the clinical outcomes of MDCT-defined LT after bAVR. Hypothesis: MDCT-defined LT might be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The risk of cusp thrombosis appears to be highest in the first year after bAVR, with a limited number of cases reported in the literature of cusp thrombosis occurring more than 1 year after placement 5 . In a meta-analysis of 4820 patients who had received either surgical aortic valve replacement or transcatheter aortic valve replacement, 452 (9.7%) had cusp thrombosis, 2 much like the patient discussed above experienced. It was noted that there was an increased risk of cerebrovascular events in those with cusp thrombosis, but the difference in risk of MI and all-cause death was not statistically significant between those with and without cusp thrombosis 2 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The risk of cusp thrombosis appears to be highest in the first year after bAVR, with a limited number of cases reported in the literature of cusp thrombosis occurring more than 1 year after placement 5 . In a meta-analysis of 4820 patients who had received either surgical aortic valve replacement or transcatheter aortic valve replacement, 452 (9.7%) had cusp thrombosis, 2 much like the patient discussed above experienced. It was noted that there was an increased risk of cerebrovascular events in those with cusp thrombosis, but the difference in risk of MI and all-cause death was not statistically significant between those with and without cusp thrombosis 2 .…”
Section: Discussionmentioning
confidence: 98%
“…1 bAVR during surgical aortic valve replacement or transcatheter aortic valve replacement (SAVR or TAVR) is an important treatment for severe symptomatic aortic valve stenosis. 2 Bioprosthetic valves are made from either human or animal tissue. Human tissue valves can be either allografts (from human cadaveric tissue) or autografts (made of the patient's own tissue).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaflet thrombosis is most commonly subclinical but has been associated with increased valve gradients and ischemic neurologic events. [17][18][19] The first large randomized study in this arena, the Global Study Comparing a rivAroxaban-based Antithrombotic Strategy to an antipLatelet-based Strategy After Transcatheter aortIc vaLve rEplacement to Optimize Clinical Outcomes, showed that in patients without an established indication for oral anticoagulation after successful TAVR, treatment strategy including rivaroxaban at a dose of 10 mg daily was associated with a higher risk of death or thromboembolic complications and a higher risk of bleeding than an antiplatelet-based strategy. 20 Interestingly, in a substudy of a trial involving patients without an indication for long-term anticoagulation who had undergone successful TAVR, a rivaroxaban-based antithrombotic strategy was more effective than an antiplatelet-based strategy in preventing subclinical leaflet motion abnormalities.…”
Section: Direct Anticoagulants In Transcatheter Aortic Valve Replacementmentioning
confidence: 99%
“…There is an increasing recognition that the incidence of early thrombus with biological valves is not insignificant ( 60 ) and that risk factors may vary with age and conditions such as atrial fibrillation ( 61 , 62 ). Tian et al ( 63 ) have discussed the relationship between hemodynamic stability and risk of adverse cerebrovascular events with bioprosthetic valves. Many cases are of a sub-clinical nature, and the presence of subclinical thrombus may be considered as an almost ubiquitous finding ( 64 ), even if associated with a small increase in rates of transient ischemic attacks with bioprosthetic valves ( 65 ); moreover, management of non-obstructive thrombus is primarily achieved by optimization of anti-coagulation ( 59 ).…”
Section: Biocompatibility Issues With Xenogeneic Pericardium and Bioprosthetic Heart Valvesmentioning
confidence: 99%